Predictors in language proficiency of young children with presumed developmental language disorder within the setting of early language intervention - Vermeij, Bernadette A. M.; Wiefferink, Carin H.; Scholte, Ron H. J.; Knoors, Harry (Frontiers in Communication, 2022)
Introduction: In the Netherlands, early language intervention is offered to children with presumed Developmental Language Disorder (DLD). The intervention is a combination of group language intervention, individual speech and language therapy and parent-implemented language intervention. During the intervention, some children show more language progress than others. It is unclear what might explain this variation. In this study, we therefore explored to what extent child, parental, and treatment factors were predictive for receptive and expressive language outcomes of young children with presumed DLD during early language intervention. Methods: Four multiple regression analyses were conducted with four child factors (pretest receptive syntax, behaviour (internalizing and externalizing), nonverbal cognitive ability and gender), one parental factor (parental stress) and one treatment factor (treatment duration) as predictors and receptive and expressive language posttest scores as outcomes. For each language posttest, the corresponding pretest language measure was also added. Data of 183 children with presumed DLD were included. Results: Receptive syntax problems were an important predictor of expressive language outcomes. Findings also showed a longer treatment duration to be a predictor of progress in expressive vocabulary. Internalizing behaviour, externalizing behaviour, nonverbal cognitive ability, gender and parental stress did not contribute to predicting language outcomes. Lower pre-intervention language scores led to lower corresponding post-intervention language scores. Conclusions. Professionals may need to be aware that children with receptive problems may be indicative of more pervasive impairment and that it can be more difficult to improve their language problems. In fact, children with receptive language problems may need both more and different approaches. The finding that the level of the pre-intervention score has an essential influence on language outcomes underlines the importance of early diagnosis and early intervention, to prevent language problems increasing.